Interferon priming is essential for human CD34+ cell-derived plasmacytoid dendritic cell maturation and function - A. Laustsen (Nature Portfolio, 2018)
Plasmacytoid dendritic cells (pDC) are an important regulator of immune responses. Here the authors show that pDC precursors, similar to peripheral blood-derived pDCs, can be differentiated from human CD34+ hematopoietic stem and progenitor cells, with type I/II IFN priming being required for their functional maturation and differentiation.